If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying db + x = 9(b + -1d) bd + x = (b * 9 + -1d * 9) bd + x = (9b + -9d) Solving bd + x = 9b + -9d Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9b' to each side of the equation. bd + -9b + x = 9b + -9b + -9d Reorder the terms: -9b + bd + x = 9b + -9b + -9d Combine like terms: 9b + -9b = 0 -9b + bd + x = 0 + -9d -9b + bd + x = -9d Add '-1x' to each side of the equation. -9b + bd + x + -1x = -9d + -1x Combine like terms: x + -1x = 0 -9b + bd + 0 = -9d + -1x -9b + bd = -9d + -1x Reorder the terms: -9b + bd + 9d + x = -9d + 9d + -1x + x Combine like terms: -9d + 9d = 0 -9b + bd + 9d + x = 0 + -1x + x -9b + bd + 9d + x = -1x + x Combine like terms: -1x + x = 0 -9b + bd + 9d + x = 0 The solution to this equation could not be determined.
| -8b-(-2b)= | | 18x+5-1+8x=46 | | 9n-5=-29+3n | | p-(-11)=11 | | 4z-22=-26+8z | | -6x-32=2 | | 12=9x+3+6 | | p+1=16 | | 60x+75y=9 | | -8+n=-7 | | (-11)-w=(-36) | | 4x-3-7=-27 | | x-(-15)=10 | | 2y-20=35 | | 4x+7+2x=-5x | | -8(9k+7)=15+3k | | 6x-8x+10=9x+19+13 | | r+8=22 | | 5x+2(x-3)+2x=6x+3(x+2)-4+x | | x+y-24=0 | | 12m=240 | | -12x-2y=-54-3x | | Kx+13-8x=-1 | | -7d-2d=-33 | | -2x+3=.5x+3 | | 2x^2=7x-29 | | 17+a=8 | | 3x-7y=6-5y | | 20n=180 | | 1=X-2x^2 | | 3d=9d-9 | | 29-3c=9(7c+2) |